Wideband dual‐band dual‐polarised antenna with less layer radiating patch. Issue 8 (26th March 2019) - Huang, Daiwei; Du, Zhengwei
Abstract : A wideband dual‐band dual‐polarised patch antenna is proposed here. It consists of a ground that has a cross slot and a rectangle hole, a feeding structure that consists of two π‐shape strips, and a radiating patch that consists of a square loop strip and a small square patch with a cross slot. Two feeding ports are used to generate two orthogonal polarisations. A prototype has been fabricated and measured. The measured −10 dB impedance operating bands of the two ports can cover the bands of 3.59–4.21 GHz and 5.42–6.34 GHz, the relative bandwidth are 15.9% and 15.6%. The measured isolations between the two ports are more than 20 and 15 dB at the lower and higher bands, respectively. The antenna has a good radiation performance at the lower and higher bands.